Nurse-facilitated reflective exercise post patient death in the ICU: a best practice implementation project. Issue 2 (5th June 2021) - VanHorn, Erica K.; Worobel-Luk, Pamela; Tanner, Ben; Jang, Hannah
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction: ICUs are stressful environments where patient care is complex and demanding; death is not an unusual outcome. Nurses can become emotionally distressed from experiencing multiple, unexpected, or traumatic patient deaths. Performing a reflective exercise immediately post death is one coping strategy which encourages healthcare staff and family to debrief their feelings in a timelier manner. Objectives: The aim of this project was to educate the nurses in the ICU with emotional coping skills pertaining to the effects of patient deaths. The objective was to implement a nurse-guided reflective exercise following each patient death in three adult ICUs in a quaternary academic medical center. Methods: The current change project used the Joanna Briggs Institute's Getting Research into Practice and Practical Application of Clinical Evidence Systems for auditing and strategy development. After standardizing the reflective exercise procedure, teaching methods were employed to support implementation. One follow-up audit measured compliance with completing a reflective exercise for all deaths occurring in the three ICUs. Contextual data were collected for completed exercises including type of death and words to describe nurses' emotions. Results: The reflective exercise script was revised and the standard procedure posted to the intranet for easy access. All ICU nurses received education on the use of this reflective exercise. For each of the two ICUs where this practice was new, compliance with nurses initiating and completing a reflective exercise was at a rate of 17 and 2%, respectively. For the ICU where reflective exercise was reintroduced, compliance was 30%. All deaths included in this study were anticipated (e.g., patient on comfort care) and calm, with the exception of one post cardiac arrest death. Conclusion: Despite multipronged teaching for why, when, and how to use reflective exercise, there was minimal success in completing reflective exercises in the two units where the practice was new. This outcome was most likely due to higher than anticipated levels of needed support or the unpredictability of frequency of deaths on each unit. However, the main achievement was having the Minute of Silence procedure with a standardized script readily available at all times for nursing staff. Reimplementation success in the other ICU was attributed to more recently established reflective practices. Further exploration of barriers, such as type of death, and re-education are essential strategies to bolster and sustain practice and to provide support for our nursing staff to prevent emotional distress.